No Guts, No Loss: Toward the Ideal Treatment for Obesity in the Twenty-First Century - Hope, David C. D.; Tan, Tricia M. M.; Bloom, Stephen R. (Frontiers in Endocrinology, 2018)
Over the last century, our understanding of the processes which control appetite and weight regulation has developed significantly. The understanding of where gut hormones fit into the control of energy homeostasis in addition to the rapid advancement of pharmacotherapeutics has paved the way for the development of novel gut hormone analogues to target weight loss. Currently, bariatric surgery remains the most efficacious treatment for Obesity. The emergence of gut hormone analogues may provide a useful non-surgical addition to the armamentarium in treating obesity. Simply targeting single gut hormone pathways may be insufficiently efficacious, and combination/multiple-agonist approaches may be necessary to obtain the results required for clear clinical impact.